Barre Matters: Hybrid Formations of Ballet and Group Fitness. (August 2021) - Markula, Pirkko
Abstract : Employing a variety of theoretical approaches, feminist researchers have critiqued the fitness industry of its singular emphasis on the impossible, narrowly defined feminine body ideal that is likely to cause more mental (e.g., body dissatisfaction) and physical ill health (eating disorders, injuries) than improve fitness. With the focus on social construction of gendered identities, there has been less problematisation of the materiality of the fitness practices and their impact on the cultural production of the moving body. In this article, I adopt a Latourian approach to seek for a more complete account of the body in motion and how it matters in the contemporary world. A barre class as a popular group exercise class that combines ballet and exercise modalities offers a location for such an examination due to the centrality of a non-human object, the barre, that distinguishes it from other group exercise classes. I consider how exercise practices may be constituted in relation to a material object, the barre, and how the physical and material intersect, historically, with the cultural politics of fitness and dance from where the barre originates. To do this, I trace the journey of the barre from ballet training to the fitness industry to illustrate how human and non-human associations create a hybrid collective.